Sulfamethoxazole+Trimethoprim Induced Stevens- Johnson Syndrome in HIV Patient: A Case Report - Gandage, Manjunath; Panumetcha, Gayathri; Patil, Neelkanthreddy; Salimath, Pooja; Kumar, Harish; Ninne, Sheetal (Indian Journal of Pharmacy Practice)
Stevens-Johnson syndrome is mucocutaneous cellmediated hypersensitivity reaction which affects 2 to 3 cases per million. SJS is generally rare, but potentially lifethreatening and commonly drug induced. Trimethoprimsulfamethoxazole (TMP/SMX) is a widely prescribed antimicrobial for the management of several uncomplicated infections. It is commonly used for the treatment and prophylaxis of Pneumocystis Jirovecii Pneumonia (PCP) in the HIV-infected population. The adverse reaction to TMP/SMX is more frequent and severe in HIV-infected patients as compared to the general population. We report a case of 39-year-old male patient admitted into male medical free ward with a chief complaints of fever, difficulty in swallowing, skin lesions over the body from 4 days. Multiple well-defined erythematous macules, Erosion and crustations on angle of the mouth, Genital Involvement, Acute Conjuctivitis are observed. These clinical manifestations are observed after taking sulfamethoxazole+trimethoprim on 5th day. Based on the above clinical investigations it is diagnosed as sulfamethoxazole+trimethoprim induced Stevens-Johnson syndrome.
Keywords: Stevens-Johnson syndrome; Sulfamethoxazole+trimethoprim; HIV; ADR.